Effect of Fruit Ripening Level and Roasting Temperature on Robusta Coffee Bean Quality - Muhari, Emma Hermawati; Sihombing, Rony Pasonang; Sarungu, Yunus Tonapa; Marlina, Ari; Leoanggraini, Unung; Hariyadi, Tri (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
The purpose of this study is to determine the effect of roasting temperature on the chemical content of Robusta coffee at various levels of Robusta coffee maturity. The research will be conducted at roasting temperatures of 190℃, 200℃, 210℃, 220℃ and chemical content analysis is carried out bygravimetric method and UV-VIS spectrophotometry on fresh beans, green beans and coffee beans at each temperature variation and the maturity level of Robusta coffee. Maturity of coffee beans will be classified visually and use an RGB meter to help and facilitate the selection of coffee beans in accordance with the level of maturity. The variables taken and observed in the study are the temperature of the roasting process, the time required at the time of roasting, as well as the mass, chemical content and physical parameters of robusta coffee beans observed before and after the roasting process. Chemical content was observed in the form of water content, fat content, caffeine, and antioxidants, then the physical parameters observed were aroma, color, shape, taste, and characteristics of coffee beans at each level of robusta coffee fruit maturity. The results obtained value of the chemical content and organoleptic test at each level of maturity of the coffee fruit and roasting temperature variations because basically the roasting temperature will produce coffee beans that have their own characteristics and flavors. This study also determines the value of the mass transfer coefficient and heat transfer in the drying process by the roasting method.